2015
DOI: 10.1073/pnas.1421536112
|View full text |Cite|
|
Sign up to set email alerts
|

Plasma butyrylcholinesterase regulates ghrelin to control aggression

Abstract: Ongoing mouse studies of a proposed therapy for cocaine abuse based on viral gene transfer of butyrylcholinesterase (BChE) mutated for accelerated cocaine hydrolysis have yielded surprising effects on aggression. Further investigation has linked these effects to a reduction in circulating ghrelin, driven by BChE at levels ∼100-fold above normal. Tests with human BChE showed ready ghrelin hydrolysis at physiologic concentrations, and multiple low-mass molecular dynamics simulations revealed that ghrelin’s first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 40 publications
1
84
0
1
Order By: Relevance
“…Plasma BChE levels have been found to be decreased in advanced cancer patients with or without hepatic involvement, despite having other normal liver function tests [19]. Recently, Chen et al reported that circulating BChE has a large impact on aggressive behavior in mice that is attributable to its ability to inactivate ghrelin [20]. In addition, circulating ghrelin concentrations are negatively correlated with body mass index in humans [21].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma BChE levels have been found to be decreased in advanced cancer patients with or without hepatic involvement, despite having other normal liver function tests [19]. Recently, Chen et al reported that circulating BChE has a large impact on aggressive behavior in mice that is attributable to its ability to inactivate ghrelin [20]. In addition, circulating ghrelin concentrations are negatively correlated with body mass index in humans [21].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (2015) recently found that elevated levels of native BChE or CocH also reduced aggression in mice, tracing such an effect to enzyme-driven inactivation of plasma ghrelin. This peptide hormone is better known for its role in hunger and feeding (Kojima et al, 1999), but it also plays a role in stress and anxiety (Carlini et al, 2002).…”
Section: Introductionmentioning
confidence: 93%
“…Delta cells also specifically expressed BCHE, which encodes butyrylcholinesterase. BCHE catalyzes the breakdown of acetylcholine and ghrelin (Chen et al 2015), thus providing a mechanism for delta cells to exert local inhibition of islet-influencing endocrine signals. PP/gamma cell-specific transcriptomes included CTD-2008P7.8, a lincRNA of unknown function; CNTNAP5, a member Table S9).…”
Section: Differential Expression Analyses Reveal Islet Cell-type-specmentioning
confidence: 99%